PLD3 epigenetic changes in the hippocampus of Alzheimer’s disease - Idoia Blanco-Luquin; Miren Altuna; Javier Sánchez-Ruiz de Gordoa; Amaya Urdánoz-Casado; Miren Roldán; María Cámara; Victoria Zelaya; María Elena Erro; Carmen Echavarri; Maite Mendioroz (Clinical Epigenetics, 2018)
Abstract Background Whole-exome sequencing has revealed a rare missense variant in PLD3 gene (rs145999145) to be associated with late onset Alzheimer’s disease (AD). Nevertheless, the association remains controversial and little is known about the role of PLD3 in AD. Interestingly, PLD3 encodes a phospholipase that may be involved in amyloid precursor protein (APP) processing. Our aim was to gain insight into the epigenetic mechanisms regulating PLD3 gene expression in the human hippocampus affected by AD. Results We assessed PLD3 mRNA expression by qPCR and protein levels by Western blot in frozen hippocampal samples from a cohort of neuropathologically confirmed pure AD cases and controls. Next, we profiled DNA methylation at cytosine-phosphate-guanine dinucleotide (CpG) site resolution by pyrosequencing and further validated results by bisulfite cloning sequencing in two promoter regions of the PLD3 gene. A 1.67-fold decrease in PLD3 mRNA levels (p value < 0.001) was observed in the hippocampus of AD cases compared to controls, and a slight decrease was also found by Western blot at protein level. Moreover, PLD3 mRNA levels inversely correlated with the average area of β-amyloid burden (tau-b = − 0,331; p value < 0.01) in the hippocampus. A differentially methylated region was identified within the alternative promoter of PLD3 gene showing higher DNA methylation levels in the AD hippocampus compared to controls (21.7 ± 4.7% vs. 18.3 ± 4.8%; p value < 0.05). Conclusions PLD3 gene is downregulated in the human hippocampus in AD cases compared to controls. Altered epigenetic mechanisms, such as differential DNA methylation within an alternative promoter of PLD3 gene, may be involved in the pathological processes of AD. Moreover, PLD3 mRNA expression inversely correlates with hippocampal β-amyloid burden, which adds evidence to the hypothesis that PLD3 protein may contribute to AD development by modifying APP processing.